2017
DOI: 10.1108/jfra-07-2016-0061
|View full text |Cite
|
Sign up to set email alerts
|

Internet financial reporting determinants: a meta-analytic review

Abstract: Purpose This study aims to examine the association between firm size, profitability, leverage, auditor type and internet reporting and investigate the moderating effect of legal system, investor protection, masculinity, economic development, construction of disclosure index and measurement proxies of independent variables. Design/methodology/approach This study conducts a meta-analytic review for 59 research papers to synthesise quantitatively the results of previous literature on the determinants of interne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
3
20

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 92 publications
(214 reference statements)
1
51
3
20
Order By: Relevance
“…A meta data analysis done by Mokhtar (2017) confirmed the prediction stressed by the agency theory, signalling theory, political cost hypothesis and innovation theory for explaining the IFR. Mokhtar (2017) found that other than size, there was a significant positive association between profitability, leverage, auditor type and Internet reporting. Therefore, it was recommended that studies on IFR consider these characteristics of firms as determinants for IFR practices.…”
Section: Internet Financial Reporting (Ifr)supporting
confidence: 54%
“…A meta data analysis done by Mokhtar (2017) confirmed the prediction stressed by the agency theory, signalling theory, political cost hypothesis and innovation theory for explaining the IFR. Mokhtar (2017) found that other than size, there was a significant positive association between profitability, leverage, auditor type and Internet reporting. Therefore, it was recommended that studies on IFR consider these characteristics of firms as determinants for IFR practices.…”
Section: Internet Financial Reporting (Ifr)supporting
confidence: 54%
“…Our findings are directly relevant to company registrars around the world. In both developed and developing markets, registrars are seeking to become more digital and are seeking new ways to improve compliance (Debreceny, Gray & Rahman, 2002;Mokhtar, 2017). Whilst governments around the world are using behavioral science to inform policies targeted at individual citizens, much less is known about how behavioral insights can influence the actions of employees within firms.…”
Section: Broader Significance Of Findingsmentioning
confidence: 99%
“…Selain itu, leverage, kepemilikan institusional, jenis industri dan profitabilitas merupakan faktor lain yang dapat mempengaruhi proses implementasi IFR. Andriyani (2017) dan Mokhtar (2017) menyatakan bahwa profitabilitas berpengaruh posiitif terhadap IFR, sehingga hasil yang diperoleh tidak sesuai dengan penelitian Chariri (2007), Agustina (2009), Hossain (2012) bahwa tidak ada hubungan secara signifikan antara profitabilitas suatu perusahaan terhadap penerapan IFR. Chariri (2007) melakukan penelitian dengan sampel perusahaaan yang terdaftar di Bursa Efek Jakarta pada tahun 2005, kecuali perusahaaan keuangan, menurutnya karena perusahaaan keuangaan memiiliki hubungan keaungan yang berbeda dengan perusahaaan lain.…”
Section: Pendahuluan Latar Belakangunclassified
“…Jika suatu perusahan memiliki ROA yang tinggi maka dapat dikatakan perusahaan tersebut cukup untuk memberikan informasi keuangan yang lebih banyak dan lebih mudah dalam melakukan bisnis IFR dengan menberikan informasi yang lengkap kepada investor dan membantu investor dalam mengambil keputusan investasi (Marston, 2003). Hasil penelitian ini juga didunkung oleh penelitian sebelumnya oleh Andriyani (2017) dan Mokhtar (2017) yang menemukan bahwa profitabilitas berpenggaruh positif terhadaap penggunaan IFR. Berdasarkan definisi tersebut dapat dirumuskan hipotesisnya seperti berikut : H1: Profitabilitas berpegaruh signifikan terhadap Internet Financial Reporting (IFR).…”
Section: Landasan Teori Dan Pengembangan Hipotesisunclassified